Transformation and Evaluation of Cry1Ac+Cry2A and GTGene in Gossypium hirsutum L. - Puspito, Agung N.; Rao, Abdul Q.; Hafeez, Muhammad N.; Iqbal, Muhammad S.; Bajwa, Kamran S.; Ali, Qurban; Rashid, Bushra; Abbas, Muhammad A.; Latif, Ayesha; Shahid, Ahmad A.; Nasir, Idrees A.; Husnain, Tayyab (Frontiers in Plant Science, 2015)
More than 50 countries around the globe cultivate cotton on a large scale. It is a major cash crop of Pakistan and is considered “white gold” because it is highly important to the economy of Pakistan. In addition to its importance, cotton cultivation faces several problems, such as insect pests, weeds, and viruses. In the past, insects have been controlled by insecticides, but this method caused a severe loss to the economy. However, conventional breeding methods have provided considerable breakthroughs in the improvement of cotton, but it also has several limitations. In comparison with conventional methods, biotechnology has the potential to create genetically modified plants that are environmentally safe and economically viable. In this study, a local cotton variety VH 289 was transformed with two Bt genes (Cry1Ac and Cry2A) and a herbicide resistant gene (cp4 EPSPS) using the Agrobacterium mediated transformation method. The constitutive CaMV 35S promoter was attached to the genes taken from Bacillus thuringiensis (Bt) and to an herbicide resistant gene during cloning, and this promoter was used for the expression of the genes in cotton plants. This construct was used to develop the Glyphosate Tolerance Gene (GTGene) for herbicide tolerance and insecticidal gene (Cry1Ac and Cry2A) for insect tolerance in the cotton variety VH 289. The transgenic cotton variety performed 85% better compared with the non-transgenic variety. The study results suggest that farmers should use the transgenic cotton variety for general cultivation to improve the production of cotton.